Highly Conductive, Ionic Liquid-Based Polymer Electrolytes. Issue 1 (7th December 2016) - Simonetti, E.; Carewska, M.; Maresca, G.; De Francesco, M.; Appetecchi, G. B.
Abstract : In this manuscript is reported a thermal and impedance spectroscopy investigation carried out on quaternary polymer electrolytes, to be addressed as separators for lithium solid polymer batteries, containing large amount of the N -methyl- N -propylpyrrolidinium bis(fluorosulfonyl)imide ionic liquid. The target is the development of Li + conducting membranes with enhanced ion transport even below room temperature. Polyethylene oxide and polymethyl methacrylate were selected as the polymeric hosts. A fully dry, solvent-free procedure was followed for the preparation of the polymer electrolytes, which were seen to be self-consistent and handled even upon prolonged storage periods (more than 1 year). Appealing ionic conductivities were observed especially for the PEO electrolytes, i.e., 1.6 × 10 −3 and 1.5 × 10 −4 S cm −1 were reached at 20 and −20°C, respectively, which are ones the best, if not the best ion conduction, never detected for polymer electrolytes.